Relation between deviated nasal septum and paranasal sinus pathology - Sumaily, Ibrahim; Hudise, Jibril; Aldhabaan, Saud (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Deviated nasal septum is a very common finding in ENT clinic, most of the times, as incidental findings without any related symptom. Sometimes it present in association with suspiciously related sinusitis. Our study is to identify the possible association between deviated nasal septum and sinusitis, so that we can consider septoplasty alone a first surgical management for these cases without any sinus procedure or not. Methods: A cross sectional case-control study. SPSS.v22 used for data analysis. We used Kuhn-Kinnedy staging system for sinus pathology and applied it on the osteomeatal complex (OMC) and all paranasal sinuses. Those patients with deviated septum were studied for sinus disease especially maxillary and anterior ethmoid sinuses, and those with sinus disease were studied for deviated septum. Results: We studied 238 patients, 120 males and 118 females, of them 164 (control) found to have central septum (68.9%) and 74 (cases) found to have deviated nasal septum (31.1%), 42 to the right and 32 to the left. 104 candidates (43.7%) found to have sinus disease. All findings were almost equal in both genders. Of the total sample, 40% of those with central septum found to have patent OMC and normal sinus mucosa equally. Of those who have DNS (74 candidates), OMC found to be opacified in 13.5% in the ipsilateral side, and 27% bilaterally. In those with DNS maxillary sinus was diseased in 20.3% ipsilaterally, 21.2% contralaterally, and 18.5% bilaterally. Anterior ethmoid sinuses were similarly affected in 40.5% ipsilateral and contralateral to DNS. Conclusions: According to our finding, no significant association between deviated nasal and paranasal sinusitis. Attributing sinuses disease to deviated nasal septum may lead to over treatment of the patient and unnecessary surgery.